The effects of selenium and vitamin E on some heamatological and biochemical values of blood in lambs - Aksakal, Mesut; Naziro?lu, Mustafa; Çay, Mehmet (Scientific and Technical Research Council of Turkey, 1996)
This study has been done to determine the effect of selenium and vitamin E on the heamotological and biochemical parameters of blood in lambs. Twelve lambs were used and divided randomly into three groups. One group was used as control. Second group was fed with selenium (Na-selenit, 0.3 mg/kg feed) and third group was fed with selenium (Na-selenit, 0.3 mg/kg feed) + vitamin E (DL-? tocopheryl acetate, 250 mg/kg feed) supplemented diet The blood biochemical and heamatological values were measured at 1st, 2nd, 4th, 6th, 10th weeks. The blood ammonia nitrogen levels of all lambs were measured three times in a day for once a week (before feeding and at the 3rd and 6th hours after feeding). The levels of serum glucose, amilase, albumin were significantly higher (P<0.05) and the activity of ALP, the levels of cholesterol and white blood cell counts were significantly lower (P<0.01. P<0.05) in both selenium and combined with vitamin E supplemented lambs than those of the control. Total protein was higher (P<0.01) in combine suplemented lambs than other two groups. Selenium and selenium plus vitamin E supplementation did not cause any changes on neutrophil, eosinophil, basophil, monocyte, lymphocyte, red blood cell counts and packet cell volume, MCV, MCH, MCHC, erythrocyte osmotic fragility and the activity of SGPT, CK, ASP and levels of triglycerides, chloride, urea nitrogen, blood ammonia nitrogen, creatinine, Ca++, phosphorus. It was observed that serum levels of glucose, amilase, albumin and total protein were increased by the supplemental selenium and selenium plus vitamin E. On the other hand the activity of ALP, level of cholesterol and white blood cell counts were decreased.
Kuzularda Selenyum - E Vitamininin Bazi Hematolojik ve Biyokimyasal De?erlere Etkisi
Keywords: Ammonia nitrogen; Biochemical levels; Heamotological values; Lambs; Selenium; Vitamin E